Word for Windows 6 : A step-by-step Guide - See, Chua Chooi (Shah Alam : Federal Publications, 1995)
This books makes it even easier by guiding you with step-by-step, easy-to-follow lessons. Each hands-on lesson can easily be completed in one sitting. You will be amazed at what you will be able to do, in no time at all, with WORD 6
Part A-Basic Skills -- Part B-Time Saving Skills -- Part C-Graphics Skills -- Part D-Formatting Skills -- Part E-Useful Skills -- Appendixes -- Index.
Includes index.
Keywords: WINDOWS (COMPUTER PROGRAM)